Taurine Antagonizes Macrophages M1 Polarization by Mitophagy-Glycolysis Switch Blockage via Dragging SAM-PP2Ac Transmethylation - Meng, Ling; Lu, Cailing; Wu, Bin; Lan, Chunhua; Mo, Laiming; Chen, Chengying; Wang, Xinhang; Zhang, Ning; Lan, Li; Wang, Qihui; Zeng, Xia; Li, Xiyi; et al. (Frontiers in Immunology, 2021)
The excessive M1 polarization of macrophages drives the occurrence and development of inflammatory diseases. The reprogramming of macrophages from M1 to M2 can be achieved by targeting metabolic events. Taurine promotes for the balance of energy metabolism and the repair of inflammatory injury, preventing chronic diseases and complications. However, little is known about the mechanisms underlying the action of taurine modulating the macrophage polarization phenotype. In this study, we constructed a low-dose LPS/IFN-γ-induced M1 polarization model to simulate a low-grade pro-inflammatory process. Our results indicate that the taurine transporter TauT/SlC6A6 is upregulated at the transcriptional level during M1 macrophage polarization. The nutrient uptake signal on the membrane supports the high abundance of taurine in macrophages after taurine supplementation, which weakens the status of methionine metabolism, resulting in insufficient S-adenosylmethionine (SAM). The low availability of SAM is directly sensed by LCMT-1 and PME-1, hindering PP2Ac methylation. PP2Ac methylation was found to be necessary for M1 polarization, including the positive regulation of VDAC1 and PINK1. Furthermore, its activation was found to promote the elimination of mitochondria by macrophages via the mitophagy pathway for metabolic adaptation. Mechanistically, taurine inhibits SAM-dependent PP2Ac methylation to block PINK1-mediated mitophagy flux, thereby maintaining a high mitochondrial density, which ultimately hinders the conversion of energy metabolism to glycolysis required for M1. This reprogramming of energy metabolism strongly opposes the conditions required for M1 polarization and tilts M2. Our findings reveal a novel mechanism of taurine-coupled M1 macrophage energy metabolism, providing novel insights into the occurrence and prevention of low-grade inflammation, and propose that the sensing of taurine and SAM availability may allow communication to inflammatory response in macrophages.